2003
DOI: 10.1016/s0733-5210(02)00139-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of waxy wheat flours: genotypic and environmental effects

Abstract: A set of waxy (amylose-free) experimental spring wheats (Triticum aestivum L.) of diverse parentage were grown, along with two nonwaxy and two partial waxy check cultivars, at diverse North American cultural environments. Grain yield and functional attributes of derived flours were determined. Average grain yield of the waxy lines did not differ significantly from the average yield of the check cultivars, but significant differences were observed amongst the waxy lines. Grain hardness varied significantly amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
53
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 21 publications
(21 reference statements)
12
53
0
1
Order By: Relevance
“…The difference of flour color between the waxy NIL and Harunoakebono was not affected by the protein content. Flour ash content of the waxy NIL was significantly higher than that of Harunoakebono; similar results were reported by Morita et al (2002b) and Graybosch et al (2003). The flour ash content is known to influence the brightness of flour.…”
Section: Estimation Of Grain and Flour Characteristicssupporting
confidence: 84%
See 2 more Smart Citations
“…The difference of flour color between the waxy NIL and Harunoakebono was not affected by the protein content. Flour ash content of the waxy NIL was significantly higher than that of Harunoakebono; similar results were reported by Morita et al (2002b) and Graybosch et al (2003). The flour ash content is known to influence the brightness of flour.…”
Section: Estimation Of Grain and Flour Characteristicssupporting
confidence: 84%
“…Flour yield and milling score of the waxy NIL were significantly lower than those of Harunoakebono. Yasui et al (1999) and Graybosch et al (2003) reported that the flour yield of waxy wheat was lower than that of non-waxy wheat. Yasui et al (1999) suggested that the beta-glucan and fat increase in waxy wheat influenced the flour yield.…”
Section: Estimation Of Grain and Flour Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This stage depends mainly on the level of amylose present, which starts the process of retrogradation. For example, for waxy wheat that contains only a low level of amylose, no increase of the curve is detected (Graybosch et al 2003).…”
mentioning
confidence: 99%
“…The discrepancies have not been well investigated. In addition, Graybosch et al (2003) found significant genetic variation in flour peak viscosities among 19 spring waxy wheats. Thus, factors other than waxy starch per se must be influencing this trait.…”
mentioning
confidence: 92%